ANALISIS KOMPARASI KINERJA KEUANGAN KOPERASI SIMPAN PINJAM DENGAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH DI DAERAH ISTIMEWA YOGYAKARTA PERIODE 2013-2017 - Suhartono Suhartono; Achmad Tjahjono (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
The purpose of this study is: to test whether there are differences in financial performance between Savings and Loans Cooperatives and Sharia Financing (KSPPS) and Conventional Savings and Loans Cooperatives (KSP) by comparing 5 (five) variables, namely: Liquidity, Solvency, Economic Rentability, Asset Growth , and Member Growth. This study uses secondary data with a total of 10 (ten) Cooperatives with details of 5 (five) Savings and Loan Cooperatives and Shari’ah Financing (KSPPS) and Conventional Savings and Loans Cooperatives (KSP) of 5 (five) with observation periods between 2013 - 2017. The statistical analysis method used is the two average differences used to test the difference in performance of the two data groups with 5 (variables) measured. The results showed that the variable Liquidity, Solvabolity, Asset Growth, and Member Growth there was no difference in performance between Savings and Loans Cooperatives and Sharia Financing (KSPPS) with Conventional Savings and Loans Cooperatives (KSP). While the Economic Rentability variable shows a difference, namely KSPSS has better performance than KSP. The limitations of this study are the shorter observation time and the small number of samples. While suggestions can be given for future research is that more research samples can be added, research variables can also be added and the research area can be expanded.